Assessing diet intake using Food Frequency data from pregnant and non-pregnant Nepali Women. - Marino-Costello, Elizabeth. (Tufts University. Tisch Library., 2019)
This poster shows assessment of diet intake using food frequency data from pregnant and non-pregnant Nepali women.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy